The Urge to Live A Comparative Study of Franz Kafka's "Der Prozess" and Albert Camus' "L'Etranger" - Rhein, Phillip H. (UNC Studies in the Germanic Languages and Literatures, 1964)
This is a penetrative and perceptive comparison of two of the most discussed novels of the twentieth century. Beginning with Camus' own appraisal of Kafka's work, the study convincingly analyzes the authors' fictive creations. Rhein is particularly intrigued by the function of time in the two authors' works, as well as their use of irony and the existentialist themes evident in their characters' pursuits. Through this exploration of theme and narrative devices, the author reveals these works as a reflection of the intellectual climate of twentieth century Europe.